Nepal : Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report, 2005)
This progress report presents key findings of the assessment of Nepal's Tenth Plan-Poverty Reduction Strategy Paper (PRSP). The report presents an overview of poverty in Nepal, the key elements of the Poverty Reduction Strategy and its linkages with the Millennium Development Goals. It discusses some of the key macroeconomic indicators and achievements. It also sums up government efforts to realign public expenditure management for supporting the PRSP goals. Achievements by sectors are documented. Performance in terms of institutional reforms and governance improvements is also described.